The association between the perception of crime and walking in gated and non-gated neighbourhoods of Asian developing countries - Gul, Yasmeen; Sultan, Zahid; Jokhio, Gul Ahmed (Elsevier Ltd, 2018)
It has been reported in the literature that the perception of crime at the neighbourhood level inversely affects the walking behaviour of individuals. On the other hand, the gated neighbourhoods are considered safe from crime, however, there is a lack of research on the association of the perception of crime and walking in gated neighbourhoods. Therefore, the objectives of the study reported in this paper were to investigate the association between the perception of crime and walking in gated and non-gated neighbourhoods. A questionnaire was used to collect the data on walking and the perception of crime in 16 neighbourhoods of Karachi Pakistan, 8 out of which were gated. Independent sample t-test and gamma tests were used for the data analysis. The results show that although there is a lower perception of crime in the gated neighbourhoods, yet the inhabitants of gated neighbourhoods engage in less physical activity comprising of walking. In spite of a greater perception of crime in non-gated neighbourhoods, higher values of walking were reported by the residents of those neighbourhoods. Therefore, it has been concluded that there does not exist a definite relationship between the perception of crime and walking behaviour at the neighbourhood level and the perceived safety from crime claimed by the proponents of the gated neighbourhoods does not encourage walking among the residents.